An evaluation of global Chikungunya clinical management guidelines: A systematic review. (December 2022) - Webb, Eika; Michelen, Melina; Rigby, Ishmeala; Dagens, Andrew; Dahmash, Dania; Cheng, Vincent; Joseph, Reena; Lipworth, Samuel; Harriss, Eli; Cai, Erhui; Nartowski, Robert; Januraga, Pande Putu; et al.
Summary: Background: Chikungunya virus (CHIKV) has expanded its geographical reach in recent decades and is an emerging global health threat. CHIKV can cause significant morbidity and lead to chronic, debilitating arthritis/arthralgia in up to 40% of infected individuals. Prevention, early identification, and clinical management are key for improving outcomes. The aim of this review is to evaluate the quality, availability, inclusivity, and scope of evidence-based clinical management guidelines (CMG) for CHIKV globally. Methods: We conducted a systematic review. Six databases were searched from Jan 1, 1989, to 14 Oct 2021 and grey literature until Sept 16, 2021, for CHIKV guidelines providing supportive care and treatment recommendations. Quality was assessed using the appraisal of Guidelines for Research and Evaluation tool. Findings are presented in a narrative synthesis. PROSPERO registration: CRD42020167361. Findings: 28 CMGs were included; 54% (15/28) were produced more than 5 years ago, and most were of low-quality (median score 2 out of 7 (range 1–7)). There were variations in the CMGs' guidance on the management of different at-risk populations, long-term sequelae, and the prevention of disease transmission. While 54% (15/28) of CMGs recommended hospitalisation for severe cases, only 39% (11/28) provided guidance for severe disease management. Further, 46% (13/28) advocated for steroids in the chronic phase, but 18% (5/28) advised against its use. Interpretation: There was a lack of high-quality CMGs that provided supportive care and treatment guidance, which may impact patient care and outcomes. It is essential that existing guidelines are updated and adapted to provide detailed evidence-based treatment guidelines for different at-risk populations. This study also highlights a need for more research into the management of the acute and chronic phases of CHIKV infection to inform evidence-based care. Funding: The UK Foreign, Commonwealth and Development Office, Wellcome Trust [215091/Z/18/Z] and the Bill & Melinda Gates Foundation [OPP1209135].